Black women, victimization, and the limitations of the liberal state. (November 2017) - Threadcraft, Shatema; Miller, Lisa L
This article challenges contemporary understandings of the US carceral state by confronting the realities of exceptionally high rates of homicide victimization among Black women and considering the implications for equality and understandings of the carceral state. We propose that neither the US state nor the US penal order can be fully understood without taking account of the exceptionally high rates of violence to which Black women are exposed. Conceptions of the carceral state that do not situate criminal justice within the larger context of raced and gendered subject formation depict criminal "justice" as an arena composed almost entirely of adult males. This obscures the realities of how state form contributes not only to criminal justice practices but also to risk of violence. Black women are uniquely situated at the intersection of risk of violence, and risk of experiencing the collateral damage of the carceral state. Without significant attention to issues of connectivity and care, which are directly affected by the carceral state and by inter-personal violence, we cannot fully understand the concepts of "carceral" or "state".